EFISIENSI PENGGUNAAN FAKTOR-FAKTOR PRODUKSI PADA USAHATANI CABAI MERAH KERITING (Capsicum annuum L.) (Studi Kasus di Kelompok Tani Prawoto Sari, Desa Munding, Kecamatan Bergas, Kabupaten Semarang) - Purry Nur Hasanah; Mahananto; Agung Prasetyo (JURNAL ILMIAH AGRINECA, 2020)
The purpose of this research were to determine the amount of production costs and income obtained from the cultivation of curly red chilli, knowing the factors of production that affect the production of curly red chilli, and to Determine an efficient use of production factors in curly red chilli farming in the Prawoto Sari Farmer Group Krajan Backwood, Munding Village, Bergas District, Semarang Regency. The method of determining the location of research using purposive or intentional methods. The sampling technique used was Random Sampling. The results showed that the average total cost incurred by farmers per farm is Rp. 10,658,731.33 or Rp. 85,269,850.64 per hectare. The average income received by farmers per farm is Rp. 11,437,101.67 or Rp. 91,496,813.36 per hectare. Based on the F test all independent variables together have a very significant effect on curly red chilli production. Based on the t test the factors of production that significantly affect production are NPK fertilizer, liquid organic fertilizer Gro-mate Ls and rotraz 200 ec insecticide. The use of production factors in curly red chilli farming has not yet reached the maximum efficient level. Inefficient factors are manure, NPK fertilizer, POC, rotraz 200 ec insecticide and mulch so that its use needs to be added. While the inefficient factor is labor, dupont lannate 25 wp insecticide and stakes, so that its use does not need to be increased or reduced.